(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Reported first in 1972, histiocytic necrotizing lymphadenitis, also known as Kikuchi- Fujimoto Disease (KFD), is an infrequent and selfrestricting disorder of lymph nodes, predominantly found in the Southeast Asian region. The common presentation of this disease is a young Asian individual presenting with painful cervical lymph node enlargement. Due to this disease’s uncommon nature, it is often misdiagnosed by clinicians as Systemic Lupus Erythematosus (SLE) malignant lymphoma, or tuberculosis. Although there are numerous hypotheses about the etiology of this illness being viral or autoimmune in nature, strong evidence is yet to be established. To let our readers to know about the disease so that we can deal patients with lymphadenopathy keeping this rare disease in our mind. Case Presentation: Here we present A 20 years-oldfemale hailing from the hill tracts of Bandarban in Bangladesh presented with three months history of rightsided inguinal lymphadenopathy, which was progressive and non-tender in nature. Associated symptom includes low-grade fever. There was no history of night sweats, weight loss, cough and no other group of lymphadenopathies. So, lymphnode biopsy done and report came as Kikuchi-Fujimoto disease. The patient made full recovery with supportive care only. Conclusion: Fever with lymphadenopathy may be due to wide range of etiologies. Although Kikuchi-Fujimoto disease is rare, it is important to diagnose it accurately. So, we can prevent further costly investigations and imaging at the same time we can avoid potential harmful treatments and psychological stress to the patient. JCMCTA 2021 ; 32 (2) : 142-146